2022
DOI: 10.21009/jdmb.06.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Repurchase Intention of Online Marketplace Customers in Jakarta with Trust as Intervening

Abstract: The COVID-19 pandemic has a significant impact on the increased consumption and using digital services of Indonesian people. One of the digital services used is an e-commerce site. This phenomenon causes intense competition between e-commerce in Indonesia. The purpose of this study was to determine the significant effect of perceived usefulness and perceived ease of use on repurchase intention through trust. Data collection method by distributing online questionnaires through Google Forms. The sample in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…This result of the research states that there is a positive and significant effect between perceived usefulness on repurchase Intention. This is increasingly proven by some research (Agag & El-Masry, 2016;Larasetiati & Ali, 2019;Nurjanah et al, 2022;Subagio et al, 2018).…”
Section: The Effect Of Perceived Usefulness On Repurchase Intentionmentioning
confidence: 88%
“…This result of the research states that there is a positive and significant effect between perceived usefulness on repurchase Intention. This is increasingly proven by some research (Agag & El-Masry, 2016;Larasetiati & Ali, 2019;Nurjanah et al, 2022;Subagio et al, 2018).…”
Section: The Effect Of Perceived Usefulness On Repurchase Intentionmentioning
confidence: 88%
“…Consumers tend to be more receptive to programs perceived as simpler than alternative applications. According to Bugembe (2010) and Nurjanah, Prabumenang, and Aditya (2023) ease of use is focused on the principle of convenience itself, which means that users can use the software easily. Karahanna, Straub, and Chervany (1999) and Roh and Park (2019) study revealed a significant positive influence of perceived ease of use on the intention of potential users to adopt the application.…”
Section: Acceptance Of Using E-hailing Grabcar Applicationmentioning
confidence: 99%
“…Temuan kami selaras dengan penelitian sebelumnya yang menunjukkan korelasi positif antara kepercayaan dan perilaku perlindungan pengguna memberikan pemahaman nuansa tentang dinamika kompleks yang mempengaruhi perilaku pengguna dalam melindungi privasi online di Indonesia (Ernawati et al, 2022;Krisnaningsih et al, 2023;Soesanto et al, 2023). Persepsi positif tentang kejelasan dan transparansi dalam kebijakan privasi, dikombinasikan dengan tingkat kepercayaan yang tinggi dan perilaku pengguna proaktif, menggambarkan gambaran dari basis pengguna yang cerdas secara digital, sadar privasi (Nurjanah et al, 2023). Dampak signifikan dari keamanan data pada kepercayaan menekankan pentingnya langkah-langkah keamanan yang kuat dalam membangun dan mempertahankan kepercayaan pengguna (Golose, 2022).…”
unclassified